Plasmodium falciparum Blood Stage Antimalarial Vaccines: An Analysis of Ongoing Clinical Trials and New Perspectives Related to Synthetic Vaccines - Salamanca, David Ricardo; Gómez, Marcela; Camargo, Anny; Cuy-Chaparro, Laura; Molina-Franky, Jessica; Reyes, César; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Frontiers in Microbiology, 2019)
Plasmodium falciparum malaria is a disease causing high morbidity and mortality rates worldwide, mainly in sub-Saharan Africa. Candidates have been identified for vaccines targeting the parasite’s blood stage; this stage is important in the development of symptoms and clinical complications. However, no vaccine is currently available which can directly affect morbidity and mortality rates. This review analyses the formulation, methodological design and results of active clinical trials for merozoite stage vaccines, regarding their safety profile, immunological response (phase Ia/b) and protective efficacy levels (phase II). Most vaccine candidates are in phase I trials and have had an acceptable safety profile. GMZ2 has made the greatest progress in clinical trials; its efficacy has been 14% in children aged less than 5 years-old in a phase IIb trial. Most of the available candidates having shown strong immunogenicity and that have been tested for their protective efficacy have provided good results when challenged with a homologous parasite strain; however, their efficacy has dropped when they have been exposed to a heterologous strain. In view of these vaccines’ unpromising results an alternative approach for selecting new candidates is needed; such line of work should be focused on how to increase an immune response induced against the highly-conserved (i.e. common to all strains), functionally relevant, protein regions that the parasite uses to invade target cells. Despite binding regions tending to be conserved, they are usually poorly antigenic and/or immunogenic, being frequently discarded as vaccine candidates when the conventional immunological approach is followed. The Fundación Instituto de Inmunología de Colombia (FIDIC) has developed a logical and rational methodology based on including conserved high activity binding peptides (cHABPs) from the main P. falciparum biologically functional proteins involved in RBC invasion. Once appropriately modified (mHABPs), these minimal, subunit-based, chemically-synthesised peptides can be used in a system covering the human immune system’s main genetic variables (the human leukocyte antigen–HLA-DR isotype) inducing a suitable, immunogenic and protective immune response in most of the world’s populations.